AKURASI ARAH KIBLAT MASJID DI DESA TINDANG KECAMATAN BONTONOMPO SELATAN KABUPATEN GOWA (STUDI PENGUKURAN DENGAN METODE SEGITIGA BOLA) - Mega wati; Alimuddin; Sohrah (HISABUNA: Jurnal Ilmu Falak, 2022)
Qibla direction is a direction that is a legal requirement and obligation that must be carried out for Muslims when carrying out prayers, based on the word of Allah swt in QS. Al-Baqarah/2: 144, QS Al-Baqarah/2: 149, QS Al-Baqarah/2: 150, as well as several hadiths and opinions of scholars who instruct Muslims to face towards the Kaaba when performing prayers. . For this reason, it is known that the Qibla direction is one of the legal requirements for prayer, it is necessary to check and determine the position of the Qibla direction of the mosque which is a place for prayer for Muslims. Especially in Tindang Village, South Bontonompo District, Gowa Regency where the majority of the local community considers that if you are facing west, it includes facing towards the Qibla. So it is considered important to re-check the position of the Qibla direction of the mosque in Tindang Village, South Bontonompo District, Gowa Regency by using the ball triangle method and Google Eart as a determinant of the accuracy of the Qibla direction of the mosques in Tindang Village by having 6 mosques which will be an illustration general position of the Qibla direction in the village. Based on the method used in determining the Qibla direction, it can be seen and found that the level of accuracy of the Qibla direction of the mosque in Tindang Village is still not accurate. This is because the results obtained from measurements of 6 existing mosques indicate that there is a deviation of more than 10 degrees to reach 20 degrees, 4 mosques have inaccurate Qibla direction and the other 2 mosques are accurate.